COVID the Catalyst for Evolving Professional Role Identity? A Scoping Review of Global Pharmacists' Roles and Services as a Response to the COVID-19 Pandemic - Kaitlyn E. Watson; Theresa J. Schindel; Marina E. Barsoum; Janice Y. Kung (MDPI AG, 2021)
The COVID-19 pandemic requires a range of healthcare services to meet the needs of society. The objective was to explore what is known about the roles and services performed by frontline pharmacists during the first year of the COVID-19 pandemic. A scoping review was conducted of frontline pharmacists' roles and services during the first year of the COVID-19 pandemic. A medical librarian conducted comprehensive searches in five bibliographic databases-MEDLINE (via Ovid), Embase (Ovid), CINAHL, Scopus, and Web of Science Core Collection for articles published between December 2019 and December 2020. The initial search retrieved 3269 articles. After removing duplicates, 1196 articles titles and abstracts were screened, 281 full texts were reviewed for eligibility, and 63 articles were included. This scoping review presents a conceptual framework model of the different layers made visible by COVID-19 of pharmacist roles in public health, information, and medication management. It is theorized that there is an invisible layer of change representing evolving professional role identity that may influence permanent role change following the pandemic. Thus, the pharmacy profession needs to build upon the lessons and experiences of this global pandemic and not let the momentum of the visible and invisible changes go to waste.